Role of Synovial Fibroblasts in Rheumatoid Arthritis - Lefevre, S.; Meier, F.M.P.; Neumann, E.; Muller-Ladner, U. (Current Pharmaceutical Design, 2015)
Rheumatoid arthritis (RA) is the most common autoimmune articular disorder. It is characterized by chronic inflammation and progressive joint destruction. As research traditionally focused on immune cells and cytokines, the role of stromal cells was addressed only to a limited extent. However, cell-cell interactions within the rheumatoid synovium alter the phenotype of synovial fibroblasts (SFs), which are nowadays considered as active and aggressive drivers in the destructive process of RA. SFs actively attach to and invade articular cartilage, thereby expressing increased amounts of adhesion molecules and proinflammatory and matrix-degrading mediators. Furthermore, RASFs stimulate synovial vascularization through the release of proangiogenic factors. As a result, angiogenesis supports the influx of immune cells into affected joints, thereby perpetuating inflammatory processes, and facilitates access of RASFs to the bloodstream, thus boosting dissemination of RA. Despite intensive research, early pathophysiological processes still remain largely unknown. In this respect, a prearthritic phase of RA is discussed. Early and intensive therapy is considered to be very effective and beneficial for long-term outcome. However, although innovative therapy and improved treatment strategies are applied to achieve clinical remission, failure of or only partial response to therapy remains common. Given that none of the currently approved therapies target RASFs, intensive research into new strategies is warranted. In this review, novel findings leading to the altered fibroblast phenotype in RA are discussed in terms of progressive inflammation and destruction. Potential novel therapeutic concepts are also addressed.
Keywords: synovial fibroblast